β-mannanase Enzyme Supplementation of Grower-Finisher Pig Diets with Copra Meal - Naldo, Michaelito A.; Bayawa, Ray Rafael S.; Seo, Beomjun (Silliman Journal, 2022)
The use of copra meal in pig diets is limited due to its high level of non-starch polysaccharides (NSP) particularly β-mannans, which act as anti-nutritional factor causing gut viscosity and consequently poor nutrient digestibility. Supplementation of β-mannanase enzyme to corn-soybean based diets has been found to improve the performance of growing pigs. This study investigated the effect of adding β-mannanase enzyme to grower-finisher pig diets with different levels of copra meal. Five hundred growing pigs (24.52 kg mean BW) were randomly allotted to eight (8) dietary treatments, in a two-stage feeding program namely grower (first 4 weeks), and finisher (succeeding 9 weeks). The first experimental diets in both grower (CM10) and finisher (CM20) stages containing 10 and 20 percent copra meal respectively were not supplemented with β-mannanase enzyme. The next experimental diets in the grower (CM10+MAN) and finisher (CM20+MAN) stages contain the same level of copra meal as in the first but were supplemented with 400 IU of β-mannanase per kg. A third set of experimental diets in the grower (CM15+MAN) and finisher (CM25+MAN) stages had higher levels of copra meal at 15 and 25 percent respectively, and were also supplemented with 400 IU of β-mannanase per kg. The fourth and last set of experimental diets for the grower (CM10+ME100) and finisher (CM20+ME100) stages contained the same level of copra meal as the first but had additional 100 kcal/kg of metabolizable energy compared to the other experimental diets. Body weight gain, feed intake, and feed per gain in the grower and finisher stages as well as for the whole duration of the study were taken and computed. No significant difference in weight gain was found among treatments in all stages but overall, diets supplemented with β-mannanase enzyme had significantly lower feed intake (P<0.05) and consequently better feed conversion. This study demonstrates the possibility of reducing cost by adding β-mannanase enzyme to diets with high levels of copra meal.